Privacy in the age of remote sensing during natural disasters in Australia and Indonesia - T. Lawal; M. Jackson; E. Georgiades (Цифровое право, 2023)
Satellites are increasingly used for remote sensing, aiding in disaster management, however they also raise privacy concerns. Despite the existence of international instruments such as the Outer Space Treaty, Principles Relating to Remote Sensing of the Earth from Outer Space and International Charter Space and Major Disasters, there are no specific rules addressing satellite misuse leading to privacy breaches during natural disasters. This article examines the existing legal frameworks for satellite regulation and privacy in Australia and Indonesia, two disaster-prone countries, with the aim of determining their adequacy for addressing privacy concerns arising from satellite use during natural disasters. By conducting a comparative analysis of both legal frameworks vis-à-vis relevant international law, this article highlights the gaps that affect their applicability and effectiveness. It finds that international rules on the use of satellites for remote sensing activities generally lack binding force, and do not address the issue of privacy breaches resulting from satellite misuse. Both countries also lack specific legal frameworks addressing privacy breaches caused by satellite misuse during disasters. It recommends that in the absence of unequivocal and specific provisions under international law, both countries could review and rely on their national legal frameworks to address potential privacy issues due to advancing remote sensing capabilities. The provision of Article VI of the Outer Space Treaty requires states to authorise and ensure continued supervision of activities of non-governmental entities in outer space. This provision could be relied on to impose, through the instrumentality of domestic laws, restrictions, or conditions on space activities, including privacy provisions. Existing space legislation requiring liability insurance could also be extended to include privacy provisions.